2022
DOI: 10.1155/2022/7754931
|View full text |Cite|
|
Sign up to set email alerts
|

Circular RNA circ-ABCB10 Promotes Proliferation and Inhibits Apoptosis of Laryngeal Carcinoma by Inhibiting KLF6

Abstract: Objective. To explore the effect of circular RNA circ-ABCB10 on the proliferation and apoptosis of laryngeal carcinoma via inhibiting KLF6. Methods. RT-qPCR assay was adopted to detect the expression of circ-ABCB10 and KFL6 in laryngeal carcinoma tissues and cell lines. Cell counting kit-8 (CCK-8) and clone formation assay were employed to detect laryngeal cancer cell viability and proliferation when circ-ABCB10 was silenced or upregulated. In this study, the apoptosis rate was detected by flow cytometry and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 35 publications
(29 reference statements)
0
1
0
Order By: Relevance
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%